The effectiveness of web-based interactive mathematics learning media in the context of floating market ethnomathematics - Akbar, Ahmad Fikri; Fajriah, Noor; Suryaningsih, Yuni (Indonesian Journal of Science and Mathematics Education, 2025)
Mathematics often appears challenging to students due to its abstract nature and traditional teaching approaches. This study evaluates the effectiveness of web-based interactive learning media within the context of floating market ethnomathematics to enhance student interest and comprehension of mathematical concepts, particularly systems of linear equations in two variables (SLETV). A pre-experimental design was employed, involving 20 eighth-grade students selected through cluster sampling. Data were collected using multiple-choice tests, observations, and interviews. The analysis utilized paired sample t-tests and N-Gain score calculations, revealing an N-Gain score of 0,421, indicating the media's effectiveness in improving student learning outcomes. A significant difference between pre-test and post-test scores confirmed the positive impact of the culturally contextualized learning approach. This method improves mathematical understanding and increases student motivation and engagement. This study implies the importance of pedagogical innovation based on local wisdom in developing contextual and meaningful learning media.